The queen of fives : a novel [large type] - Hay, Alex (Writer) (Thorndike Press large print historical fiction., 2025)
"1898. Quinn le Blanc, London's most talented confidence woman, has five days to pull off her most ambitious plot yet: trap a highly eligible duke into marriage and lift a fortune from the richest family in England. Masquerading as the season's most enviable debutante, Quinn puts on a brilliant act that earns her entrance into the grand drawing rooms and lavish balls of high society--and propels her straight into the inner circle of her target: the charismatic Kendals. Among those she must convince are the handsome bachelor heir, the rebellious younger sister, and the esteemed duchess eager to see her son married. But the deeper she forges into their world, the more Quinn finds herself tangled in a complicated web of love, lies, and loyalty. The Kendals all have secrets of their own, and she may not be the only one playing a game of high deception ..." --